Changes in production work when using smart wearables—results of a~Delphi-based study; Veränderungen der Produktionsarbeit beim Einsatz von Smart Wearables~– Ergebnisse einer Delphi-basierten Studie - Verena Blumberg; Eva-Maria Schulte; Simone Kauffeld (Zeitschrift für Arbeitswissenschaft, 2021)
In industrial production, smart wearables (e.g. data glasses) are becoming more relevant to support employees. While economic aspects have so far been the focus of the introduction, changes for work design have been neglected. The aim of the Delphi study was to describe changes through the use of smart wearables and to derive implications for work design. Six description dimensions (application, implications for work design, data use, personalization, flexibility, introductory purpose) were identified and 18~scenarios were developed. The assessment of the scenarios in terms of desirability and degree of dissemination showed that scenarios for work-related and ergonomic support are particularly desirable and scenarios for changes in cooperation are considered particularly likely. Data usage is a~relevant factor for the assumed degree of dissemination but not for the assessment of desirability. In operational practice, work design and economic aspects are important for assessing the scenarios. Practical Relevance: The results show possible development scenarios for production work when using smart wearables and highlight possible implications for work design. Positive and negative effects on task, knowledge, social and contextual characteristics are identified, which offer suggestions for a~conscious selection and design of the use of technology in practice.
Keywords: 650; Digitalization; Smart wearables; Industry~4.0; Work design; Delphi method; Digitalisierung; Technologie; Industrie~4.0; Arbeitsgestaltung; Delphi-Methode